FAKTOR YANG MEMPENGARUHI PRICE TO BOOK VALUE - MUWAFICK HIDAYAT (Jurnal Bisnis dan Akuntansi, 2018)
The purpose of this research is to empirically test and analyze the influence of dividend payout ratio, current ratio, return on asset, firm size, debt to equity ratio and asset growth. The object of this research is food and beverages companies listed in Indonesia Stock Exchange in 2011-2016 period. The sample consisting of 7 companies, was selected by means of the purposive sampling technique. The research data is secondary data obtained from Indonesia Stock Exchange (IDX). The results of this research showed that current ratio, return on asset, firm size, debt to equity ratio influence the firm value, while dividend payout ratio and asset growth have no influence on firm value.